Meningkatkan Hasil Belajar Mata Pelajaran Dasar Listrik Melalui Pendekatan Kontekstual untuk Sekolah Menengah Kejuruan - Pambudi, Dewa Cahya; Purtanto, Hari; Wicaksono, Arif (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2025)
Several challenges were identified during classroom observation and consultation with the mentor teacher in Grade X of the Electrical Power Installation Engineering program. These challenges included low student interest in learning, particularly in foundational subjects, which often led to confusion and frequent questions during practical sessions. Limited understanding was found to negatively affect both theoretical achievement and practical skills performance. In addition, many students expressed a lack of interest in learning because they perceived the material as irrelevant to their daily lives. To address these issues, a contextual teaching approach was implemented. This approach links learning materials with students’ everyday experiences, aiming to make learning more relevant and meaningful. The implementation was carried out through two cycles of classroom action research. During the initial stage, only a small proportion of students were able to meet the minimum mastery criteria. After applying contextual teaching combined with the Problem-Based Learning model, student achievement showed notable improvement, although not all students had reached the expected level. In the following cycle, contextual teaching was integrated with the Project-Based Learning model, which resulted in a more significant improvement, with all students successfully surpassing the expected level of competence. These findings indicate that contextual teaching can effectively enhance students’ learning outcomes and support them in achieving the required competence levels set by SMK Nasional Malang.